Utilizing Artificial Intelligence for Personalized Arabic Language Learning Plans - Ibnu Fitrianto; Cahya Edi Setyawan; Malikus Saleh (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study investigates the utilization of artificial intelligence (AI) in designing personalized Arabic language learning plans tailored to individual needs. In the context of evolving globalization, the demand for strong Arabic language proficiency is increasing, prompting the need for more adaptive and effective learning approaches. In this research, an AI-based learning approach is employed to provide personalized learning experiences, considering individual learning styles, proficiency levels, and preferences. Through surveys, interviews, and field testing, the study analyzes the effectiveness and potential of AI technology in enhancing motivation, engagement, and learning outcomes in Arabic language education. The findings indicate that AI-driven personalized learning approaches can enhance satisfaction and learning achievements among participants, while promoting inclusivity and accessibility in Arabic language education. The implications of this research for education and the development of more adaptive and personalized curricula are also discussed.